Proceedings of the 7th International Conference on PErvasive Technologies Related to Assistive Environments 2014
DOI: 10.1145/2674396.2674408
|View full text |Cite
|
Sign up to set email alerts
|

Tell me your apps and I will tell you your mood

Abstract: Bipolar Disorder is a disease that is manifested with cycling periods of polar episodes, namely mania and depression. Depressive episodes are manifested through disturbed mood, psychomotor retardation, behaviour change, decrease in energy levels and length of sleep. Manic episodes are manifested through elevated mood, psychomotor acceleration and increase in intensity of social interactions. In this paper we report results of a clinical trial with bipolar patients that amongst other aspects, investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Several mobile solutions have been proposed to utilize a self-monitoring and intervention-based treatment of depression [2-5]. One particular research approach adopted by many research groups has been to investigate how objectively measured behavioral features such as “location” and “social interaction” correlate with depression; using this approach, they have tried to differentiate euthymic and depressed states [6-11]. For example, using a mobile phone app passively recording information from sensors in the phone, Saeb et al [7] could show a statistically significant correlation between 6 different objective features, including mobile phone usage frequency and self-assessed mood using the Patient Health Questionnaire-9 (PHQ-9) scale [12] in nonclinical samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mobile solutions have been proposed to utilize a self-monitoring and intervention-based treatment of depression [2-5]. One particular research approach adopted by many research groups has been to investigate how objectively measured behavioral features such as “location” and “social interaction” correlate with depression; using this approach, they have tried to differentiate euthymic and depressed states [6-11]. For example, using a mobile phone app passively recording information from sensors in the phone, Saeb et al [7] could show a statistically significant correlation between 6 different objective features, including mobile phone usage frequency and self-assessed mood using the Patient Health Questionnaire-9 (PHQ-9) scale [12] in nonclinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found statistically significant correlations between objective behavioral features collected from mobile and wearable devices and mood symptoms in nonclinical samples of participants without psychiatric illnesses [14-17] as well as in clinical samples of patients diagnosed with psychiatric disorders [11,18-20]. …”
Section: Introductionmentioning
confidence: 99%
“…Smartphone logs are key input for research aimed at understanding different dimensions of mobile communication, from smartphone use (Böhmer et al, 2011) or general communication behaviours (Wagner et al, 2013) to the way in which given contexts shape them (Karikoski & Soikkeli, 2013). At the intersection of social sciences and computer sciences, mobile logs help to predict selected human behaviour dimensions, including human stress (Ferdous et al, 2015), bipolar disorder states (Alvarez-Lozano et al, 2014) and other personality traits (De Montjoye et al, 2013). In the following, we describe the biases identified in this area.…”
Section: Smartphone Log Collectionmentioning
confidence: 99%
“…Shared use is difficult to grasp, and it becomes more relevant when logs are used for psychometric predictions, e.g. [76][77][78], as they refer to a single user. Therefore, similarly to the questioning of self-reported use not being 'objective data,' tracked use also faces interpretive challenges as it is a proxy of usage not fully representing actual human use.…”
Section: Data Interpretationmentioning
confidence: 99%